1996
DOI: 10.1093/njaf/13.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Formulas for Estimating Volumes of Butt Logs of Appalachian Hardwoods

Abstract: A database comprising measurements of over 700 trees and logs of Appalachian hardwoods was used to compare the performance of five formulas (Newton, Huber, Smalian, Bruce, and that of the centroid method)for estimating the volumes of butt logs. In terms of bias and precision, the centroid method was clearly superior to all other methods. Bruce's formula performed better than Smalian's formula and is recommended for use when only the ends of butt logs are accessible for measuring diameter, as in log stacks. Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Smalian's formula uses cross sectional area at the large end of the log (B) and at the small end of the log (S), and log length (L) to estimate log volume: Smalian: V= ((B+S)/2) L………………………….….. 1Smalian's equation is fairly accurate for upper logs, but tends to greatly overestimate the volume of butt logs Wiant et al (1996).…”
Section: Smalian's Formulamentioning
confidence: 99%
“…Smalian's formula uses cross sectional area at the large end of the log (B) and at the small end of the log (S), and log length (L) to estimate log volume: Smalian: V= ((B+S)/2) L………………………….….. 1Smalian's equation is fairly accurate for upper logs, but tends to greatly overestimate the volume of butt logs Wiant et al (1996).…”
Section: Smalian's Formulamentioning
confidence: 99%
“…The result showed that equations of comparisons have no-significant result, Newton`s formula was superior to all other method in estimating of volume of the logs of wood. (Wiant et al, 1996) used five formulas (Newton, Huber, Smalians, Bruce, and Centroid) for estimating the volume of butt logs of Appalachian hardwoods (Quercus rubra, Quercus alba, Liriodendron tulipifera, Acer rubrum, and miscellaneous spp.) in West Virginia.…”
Section: Introductionmentioning
confidence: 99%